2017
DOI: 10.1016/j.amjmed.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Red Yeast Rice Preparations: Are They Suitable Substitutions for Statins?

Abstract: Red yeast rice, a commercially available food supplement known to reduce serum cholesterol, has been repeatedly advocated as alternative therapy for hypercholesterolemic patients that refuse statins, cannot tolerate statin therapy's side effects, or request a "naturopathic" medicine. Red yeast rice contains a fungus (Monascus purpureus), which was utilized in the original production of lovastatin (MEVACOR, Merck & Co, Whitehouse Station, NJ), the first marketed pharmaceutical statin, and is chemically identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…Red yeast rice (RYR), a nutraceutical that inhibits HMG-CoA reductase and reduces LDL-C [ 52 ], is used by some patients who are intolerant to statins [ 53 ]. It is enzymatically hydrolysed in the small intestine and liver by cytochrome P450.…”
Section: Recommendationsmentioning
confidence: 99%
“…Red yeast rice (RYR), a nutraceutical that inhibits HMG-CoA reductase and reduces LDL-C [ 52 ], is used by some patients who are intolerant to statins [ 53 ]. It is enzymatically hydrolysed in the small intestine and liver by cytochrome P450.…”
Section: Recommendationsmentioning
confidence: 99%
“…Because nutraceuticals are not regulated as drugs, red rice supplements are not always subjected to strict adverse event monitoring programs. Physicians should make patients aware of potential risk factors related to the use of RYR nutraceuticals to ensure safety, lack of allergenic compounds, and potential untoward effects (Dujovne 2017).…”
Section: Untoward Effectsmentioning
confidence: 99%
“…In addition, it is also not easy to predict or understand the side effect risks of RYR because of the high variability in monacolin content in various commercial RYR dietary supplements. [36][37][38] Unlike the dietary supplement, it was suggested that the content of RYR prescriptions with good manufacturing practice were relatively stable and safe, such as Xuezhikang, HypoCol, and LipoCol Forte. [13][14][15]29 A clinical trial suggested that there were no differences between the HypoCol group and the placebo group with regard to glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%